Quantitative Evaluation of Passive Muscle Stiffness in Chronic Stroke. (December 2016) - Eby, Sarah; Zhao, Heng; Song, Pengfei; Vareberg, Barbara J.; Kinnick, Randall; Greenleaf, James F.; An, Kai-Nan; Chen, Shigao; Brown, Allen W.
ABSTRACT: Objective: The aim of this study was to evaluate the potential for shear wave elastography (SWE) to measure passive biceps brachii individual muscle stiffness as a musculoskeletal manifestation of chronic stroke. Design: This was a cross-sectional study. Nine subjects with stroke were evaluated using the Fugl-Meyer and Modified Ashworth scales. Electromyography, joint torque, and SWE of the biceps brachii were obtained during passive elbow extension in subjects with stroke and four controls. Torque values at the time points corresponding to each SWE measurement during all trials were selected for direct comparison with the respective SWE stiffness using regression analysis. Intraclass correlation coefficients (ICC(1, 1)) were used to evaluate the reliability of expressing alterations in material properties. Results: Torque and passive stiffness increased with elbow extension—minimally for the controls and most pronounced in the contralateral limb of those with stroke. In the stroke group, several patterns of shear moduli and torque responses to passive elbow extension were identified, with a subset of several subjects displaying a very strong torque response coupled with minimal stiffness responses ( y = 2.712 x + 6.676; R 2 = 0.181; P = 0.0310). Values of ICC(1, 1) indicate consistent muscle stiffness throughout testing for the dominant side of controls, but largely inconsistent stiffness for other study conditions. Conclusions: SWE shows promise for enhancing evaluation of skeletal muscle after stroke. The wide variability between subjects with stroke highlights the need for precise, individualized measures.